Pengaruh Financial Distress, Audit Tenure, dan Profitabilitas terhadap Penerimaan Opini Audit Going Concern dengan Persistensi Laba sebagai Variabel Moderasi - Siti Ghozinatul Jannah; Nera Marinda Machdar (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2024)
The aim of this study is to examine the interconnection between financial distress, audit tenure, and profitability concerning the endorsement of the going concern audit opinion, with earnings persistence serving in a moderating role. The method applied in this study is descriptive statistical analysis with a numerical methodology. The findings of the research suggest that the duration of audit tenure and the level of profitability negatively exert an impact on approval of the going concern audit opinion. Conversely, financial distress has been demonstrated to possess a substantial impact on the acceptance of going concern audit opinions. Furthermore, the persistence of earnings intensifies the impact of financial distress and profitability on the approval of the audit opinion regarding the entity's ability to continue its operations, whereas it diminishes the impact of audit tenure on the approval of the going concern audit opinion.